2018
DOI: 10.1007/s00429-018-1675-4
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure mediates the association between height and cognitive ability

Abstract: Height and general cognitive ability are positively associated, but the underlying mechanisms of this relationship are not well understood. Both height and general cognitive ability are positively associated with brain size. Still, the neural substrate of the height-cognitive ability association is unclear. We used a sample of 515 middle-aged male twins with structural magnetic resonance imaging data to investigate whether the association between height and cognitive ability is mediated by cortical size. In ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
(96 reference statements)
1
13
0
Order By: Relevance
“…In humans, there are many genetic correlations between height and psychiatric, behavioral and personality traits, including neuroticism 55 , risk tolerance 56 and smoking cessation 57 . There is also strong evidence that body size is associated with differences in brain structure in humans and dogs, and that those have functional effects (most commonly reported in the area of cognition) 11,58 . Both Insulin/IGF signaling and downstream pathways (here incl.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there are many genetic correlations between height and psychiatric, behavioral and personality traits, including neuroticism 55 , risk tolerance 56 and smoking cessation 57 . There is also strong evidence that body size is associated with differences in brain structure in humans and dogs, and that those have functional effects (most commonly reported in the area of cognition) 11,58 . Both Insulin/IGF signaling and downstream pathways (here incl.…”
Section: Discussionmentioning
confidence: 99%
“…We also report a significant positive association between MO in the medial lemniscus and height. However, although previous studies have similarly identified a positive link between height and intact WM integrity [99], we also consider alternative interpretations that may have produced similar findings. Namely, as described in the case of [93], the observed co-localized increases in MO and FA in the medial lemniscus may indicate evidence of selective degeneration of secondary WM tracts which result in the “spared” fibers of this sub-region establishing a newly acclaimed primary eigenvector, and with it a misleading increase in both FA and MO [40].…”
Section: Discussionmentioning
confidence: 77%
“…In humans, there are many genetic correlations between height and psychiatric, behavioral and personality traits, including neuroticism [ 59 ], risk tolerance [ 60 ] and smoking cessation [ 61 ]. There is also strong evidence that body size is associated with differences in brain structure in humans and dogs, and that those have functional effects (most commonly reported in the area of cognition) [ 11 , 62 ]. Both Insulin/IGF signaling and downstream pathways (here incl.…”
Section: Discussionmentioning
confidence: 99%